Understanding neuropsychiatric symptoms in Alzheimer’s disease: challenges and advances in diagnosis and treatment - Pless, Andrew; Ware, Destany; Saggu, Shalini; Rehman, Hasibur; Morgan, John; Wang, Qin (Frontiers in Neuroscience, 2023)
Neuropsychiatric symptoms (NPS) in Alzheimer’s disease (AD) affect up to 97% of AD patients, with an estimated 80% of current AD patients experiencing these symptoms. Common AD-associated NPS include depression, anxiety, agitation and aggression, and apathy. The severity of NPS in AD is typically linked to the disease's progression and the extent of cognitive decline. Additionally, these symptoms are responsible for a significant increase in morbidity, mortality, caregiver burden, earlier nursing home placement, and greater healthcare expenditure. Despite their high prevalence and significant impact, there is a notable lack of clinical research on NPS in AD. In this article, we explore and analyze the prevalence, symptom manifestations, challenges in diagnosis, and treatment options of NPS associated with AD. Our literature review reveals that distinguishing and accurately diagnosing the NPS associated with AD remains a challenging task in clinical settings. It is often difficult to discern whether NPS are secondary to pathophysiological changes from AD or are comorbid psychiatric conditions. Furthermore, the availability of effective pharmaceutical interventions, as well as non-pharmacotherapies for NPS in AD, remains limited. By highlighting the advance and challenges in diagnosis and treatment of AD-associated NPS, we aspire to offer new insights into the complexity of identifying and treating these symptoms within the context of AD, and contribute to a deeper understanding of the multifaceted nature of NPS in AD.